Dissipation Kinetics Study of Clopyralid in Water - Singh, Anand; Tandon, Shishir; Sand, N.K. (Asian Journal of Chemistry, 2016)
The study was undertaken to study the dissipation kinetics of clopyralid in water under laboratory conditions. Water was fortified with clopyralid at 150 μg a.i. per liter and sampling was done at different time interval after application. Residue was estimated by reversed phase HPLC with UV detector at 229 nm. Dissipation study showed that clopyralid degraded with decay rate (l = 0.06 ± 0.02/days) in water and no detectable residue was found on 30th day of application. Dissipation in water followed monophasic first order kinetics. The half life of clopyralid in the water was found to be 11.55 days. The limit of detection was 5 ng/mL of water and the RSD was 1.87 %.